2021
DOI: 10.1080/17518253.2021.1923824
|View full text |Cite
|
Sign up to set email alerts
|

Green-based bio-synthesis of nickel oxide nanoparticles in Arabic gum and examination of their cytotoxicity, photocatalytic and antibacterial effects

Abstract: In the current paper, NiO-NPs were synthesized through a sol-gel method by the usage of a biocompatible polymer known as Arabic gum (GA) as a stabilizing agent. The structural, optical, and magnetic properties of the obtained product was investigated by the application of TGA/ DTA, FT-IR, UV-Vis, XRD, FESEM/EDX, and VSM analyzes. The FESEM images of NiO-NPs displayed its spherical shape and average size of about 59 nm. The antimicrobial activity of NiO-NPs was investigated against Gram-positive bacteria includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“… 13,14 Previous studies have reported that RGO has antimicrobial activity, 15–17 and GO when conjugated with active ingredients exhibits antimicrobial and antinematodal activities. 18,19 Furthermore, metal and metal oxide nanoparticles, such as silver, 20–22 zinc oxide, 23–25 and nickel oxide, 26,27 are widely used as antimicrobials, and a silver boron nano-formulation is a potential nematicide. 28 …”
Section: Introductionmentioning
confidence: 99%
“… 13,14 Previous studies have reported that RGO has antimicrobial activity, 15–17 and GO when conjugated with active ingredients exhibits antimicrobial and antinematodal activities. 18,19 Furthermore, metal and metal oxide nanoparticles, such as silver, 20–22 zinc oxide, 23–25 and nickel oxide, 26,27 are widely used as antimicrobials, and a silver boron nano-formulation is a potential nematicide. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Functionalized Arabic gum (frequently associated to other biopolymer) has also been investigated for metal sorption [25,[35][36][37][38][39][40]. Arabic gum was also used as support for designing active materials with antimicrobial properties by deposition of metal oxide nanoparticles [41].…”
Section: Characterization Of Sorbentmentioning
confidence: 99%
“…Among all the nano catalysts, PMNPs are specifically appealing because of their high surface area to extent ratios and excellent surface properties, which allowed their catalytic performance to be available. [112] Since catalytic reactions required transition metals, polysaccharides could provide suitable functional properties for dispersing the noble MNPs as hosts and make the dimensions and form of catalysts extra controllable. [1] Thus, numerous studies had highlighted the possibilities of PMNPs in the catalytic application as shown in .…”
Section: Biopolymers For Catalytic Reductionmentioning
confidence: 99%
“…In this regard, homogeneous catalysts that exhibited excessive selectivity had acquired a whole lot of extra interest. Among all the nano catalysts, PMNPs are specifically appealing because of their high surface area to extent ratios and excellent surface properties, which allowed their catalytic performance to be available [112] . Since catalytic reactions required transition metals, polysaccharides could provide suitable functional properties for dispersing the noble MNPs as hosts and make the dimensions and form of catalysts extra controllable [1] .…”
Section: Biopolymers For Catalytic Reductionmentioning
confidence: 99%